Techniques to improve the maintenance of a laboratory colony of Nyssomyia neivai (Diptera: Psychodidae) - Goulart, Thais Marchi; Castro, Camila Feitosa de [UNESP]; Machado, Vicente Estevam [UNESP]; Silva, Flávia Benini da Rocha [UNESP]; Pinto, Mara Cristina [UNESP] (BioMed Central, 2015)
The most critical phase in sand fly colonization is the high mortality in the larval instars. In this study, we sought out strategies for improving the colonization of Nyssomyia neivai, one of the vectors of cutaneous leishmaniasis agent in South America. A colony of Ny. neivai was established in the laboratory from a field population, and the productivity of adults was evaluated considering carrying capacity, diet for larvae and surface for oviposition. The highest emergency rate of adults was achieved with the fewest couples inside 150 mL rearing chambers on a sterilized diet made of rabbit feces, rabbit food, soil and fish food and with vermiculite as a substrate for oviposition and the development of larvae. Our data on Ny. neivai colonization showed that the best adult productivities were achieved with fewer couples inside the rearing chambers; smaller rearing containers of 150 mL (due to less fungi growth); sterilized diet made of rabbit feces, rabbit food, soil and fish food; and vermiculite as the substrate for oviposition and development of larvae.
Keywords: Sand flies; Phlebotomine; Immature stages; Larval diet; Nyssomyia neivai; Substrates; Sterilized diet